Latitudinal cline in the foraging dichotomy of loggerhead sea turtles reveals the importance of East China Sea for priority conservation. (8th April 2022) - Okuyama, Junichi; Watabe, Akemi; Takuma, Shunichi; Tanaka, Kentaro; Shirai, Kotaro; Murakami‐Sugihara, Naoko; Arita, Mamiko; Fujita, Kento; Nishizawa, Hideaki; Narazaki, Tomoko; Yamashita, Yoshiya; Kameda, Kazunari
Abstract: Aim: Quantifying the importance of habitat areas for conservation of highly migratory marine species with complex life histories can be challenging. For example loggerhead turtles ( Caretta caretta ) nesting in Japan forage both oceanically and neritically after their reproductive period. Here, we aimed to quantify the proportions of turtles using these two contrasting habitats (foraging dichotomy) to suggest priority conservation areas. Location: North Pacific Ocean. Methods: We examined the occurrence of foraging dichotomy at three nesting sites (Ishigaki, Okinoerabu Islands and Ichinomiya) based on stable isotope analysis of the egg yolks for 82 turtles and satellite tracking of post‐nesting migration for 12 turtles. Moreover, we used the data of three other sites from previous studies (Yakushima Island, Minabe and Omaezaki). Results: Two neritic foraging grounds (East China Sea and the coastal area of the Japanese archipelago), and an oceanic ground (North Pacific Ocean) were identified. We found a latitudinal cline with respect to the occurrence of foraging dichotomy; >84% of the females nesting at southern sites (Ishigaki and Okinoerabu Islands), 73% at middle sites (Yakushima Island and Minabe) and <46% at northern sites (Omaezaki and Ichinomiya) were neritic foragers; the proportion of oceanic foragers increased at northern sites. Based on the annual number of nests in the entire nesting region of Japan, satellite tracking and the latitudinal cline of foraging dichotomy, we estimated that 70% and 9% of annual nesting females in Japan utilize the neritic foraging habitat in the East China Sea and the coastal area of the Japanese archipelago, respectively, and that and 22% utilize the oceanic habitat of the North Pacific Ocean. Main conclusions: The East China Sea represents a critical foraging habitat for the North Pacific populations of endangered loggerhead sea turtles. Our findings emphasize the need for international management to ensure their protection.